EMPOWERMENT OF COASTAL WOMEN THROUGH SELF-HELP GROUPS IN THOOTHUKUDI DISTRICT - DR.CISMA.F, DR.R.SIVASANKARI (South Eastern European Journal of Public Health, 2025)
Women empowerment is an important key factor which improves the economic, social, education, health and decision making skills among women. Many studies have been conducted regarding the empowerment of women through self help groups and thousands of the women in India are building their lives, their families and their society through Self-help groups. In this study an attempt has been made to identify the empowerment of coastal women through self help groups. 60 sample respondents from the study area have been identified and collected data were analysed through percentage analysis and found out that women has been improved in their personal, social status, economic and financial inclusion. The study also identified that there is no livelihood diversification as per the opinion of sample respondents.